Implementasi E-Court di Pengadilan Negeri Denpasar Kelas 1A Sebagai Perwujudan Reformasi Birokrasi (Studi Kasus: Penanganan Perkara Perdata) - Amalo, Romando Alexander (Socio-political Communication and Policy Review, 2024)
This study examines the success of e-Court implementation in Denpasar District Court in handling civil cases as an embodiment of bureaucratic reform. The process of measuring the success of implementation uses qualitative research methods, where data is taken directly through direct observation activities in the object of research and literature study. The results of the study show that the implementation of e-Court in the District Court appears to be running in accordance with the policy directions written in the legal basis for its implementation, but there is still a need for improvement and optimization. There are still obstacles especially in the technical introduction of this service to the public, especially those who are not registered as an advocate (registered users). Innovation in promotion and digital communication to the public needs to be improved. This is done so that this policy can be fully absorbed and used optimally to further improve the development of this service in the future for an increasingly advanced judiciary. Abstrak Penelitian ini melihat keberhasilan implementasi e-Court di Pengadilan Negeri Denpasar dalam penanganan perkara perdata sebagai perwujudan reformasi birokrasi. Proses pengukuran keberhasilan implementasi menggunakan metode penelitian kualitatif, dimana data diambil langsung melalui kegiatan observasi langsung di objek penelitian dan studi pustaka. Hasil penelitian menunjukkan bahwa implementasi e-Court di Pengadilan Negeri tampak berjalan sesuai arahan kebijakan yang tertulis dalam dasar hukum pelaksanaannya, namun masih perlu adanya peningkatan dan pengoptimalan. Masih ditemukan kendala terlebih terhadap pengenalan teknis layanan ini kepada masyarakat terutama yang bukan terdaftar sebagai seorang advokat (pengguna terdaftar). Inovasi dalam promosi dan komunikasi digital ke masyarakat dirasa perlu ditingkatkan. Hal ini dilakukan agar kebijakan ini dapat diserap secara penuh dan dipakai dengan optimal guna semakin meningkatkan pengembangan layanan ini kedepannya bagi peradilan yang semakin maju. Kata kunci: Implementasi, e-Court, Perkara Perdata